Mercury and health in Madre de Dios, Peru - Osores Plenge, Fernando (2010)
Mercury is an essential element for extracting gold from river beds in illegal gold mining in Madre de Dios Region in Peru. Water pollution by mercury has become a very serious public health problem for this area, because of the dissemination of this metal in the food chain and being humans the final destination of mercury. Exposure to this element in pregnant women may lead to chronic mercury poisoning, and fetuses and embryos may become irreversibly affected, with the occurrence of congenital neurological disorders.